Analysis of Motivations that Influence the Interest of Accounting bachelor’s degree Candidates Enrolling Study at PPAk in Indonesia - Indriaty, Lely; Ayusmar; Thomas, Gen Norman (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the motivations that influence the interest of Accounting bachelor’s degree Candidates to enroll study at PPAk in Indonesia. There are four motivations tested in this research: career motivation, social motivation, economic motivation and cost motivation. The research uses a quantitative descriptive method, with multiple regression equations analysis using SPSS 24. The population in this study are accounting undergraduate students from 2 different Higher Educations in Jakarta. Data collected by giving questioner to 100 respondents. The results of this study indicate that career motivation produces a significance value of 0.002 <0.05, but social motivation of 0.563> 0.05. Economic motivation of 0.925> 0.05, and cost motivation of 0.136> 0.05. Based on findings, it concludes that career motivation has more positive and significant than social motivation, economic motivation and cost motivation to influence the interest of accounting bachelor’s degree candidates to enroll Study at PPAk in Indonesia. Therefore, the conclusion implies that the career motivation must be considered in improving the quality of PPAk curriculum in Indonesia.